Implementation Of Workforce Placement Policy In The Field Of Placement And Expansion Of Job Opportunities Of The Manpower And Transmigration Service Of Bengkulu Province: Implementasi Kebijakan Penempatan Tenaga Kerja Pada Bidang Penempatan Dan Perluasan Kesempatan Kerja Dinas Ketenagakerjaan Dan Transmigrasi Provinsi Bengkulu - Irvan Lufti Maulana; Bobby Mandala Putra; Henny Aprianty (Gayaku Publisher, 2025)
Unemployment remains a significant challenge in labor development in Bengkulu Province, highlighting the need for effective labor placement policies to improve employment opportunities. This study aims to analyze the implementation of the Minister of Manpower Regulation Number 39 of 2016 concerning Labor Placement at the Placement and Job Expansion Division of the Bengkulu Province Manpower and Transmigration Office and to identify the supporting and inhibiting factors affecting its implementation. This research employed a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation involving key informants, including government officials, implementing staff, company representatives, and job seekers. Data were analyzed using the Miles and Huberman interactive model supported by NVivo 12 software. The findings indicate that the implementation of the labor placement policy has generally been effective based on George Edward III’s policy implementation dimensions, namely communication, resources, disposition, and bureaucratic structure. Communication among implementers and stakeholders was conducted effectively through various information channels and employment programs. The availability of resources, authority, information, and facilities supported policy implementation; however, challenges remained in terms of limited human resources and the mismatch between job seekers’ competencies and labor market demands. Supporting factors included collaboration with companies, training institutions, and the utilization of information technology, while inhibiting factors consisted of limited human resources, competency gaps among job seekers, and the uneven dissemination of employment information across several regions. Therefore, strengthening coordination, enhancing workforce competencies, and expanding access to employment information are necessary to improve the effectiveness of labor placement policy implementation.